LED supplementary strategy based on hourly light integral for improving the yield and quality of greenhouse strawberries - Yang, Ruimei; Qiu, Chenhui; Zheng, Jianfeng; Ji, Fang; He, Dongxian; Yang, Po (International Journal of Agricultural and Biological Engineering, 2024)
Supplemental lighting is critical to the growth of greenhouse crops under the environmental conditions of low temperatures combined with weak radiation during the winter and spring seasons. To achieve the essential daily light integral (DLI) for greenhouse crop growth, a supplemental light strategy was proposed based on hourly light integral (HLI). The target HLI was calculated by dividing the target DLI by the duration of light exposure, while the actual HLI was obtained by accumulating the Photosynthetic Photon Flux Density (PPFD) based on real-time monitoring. Subsequently, the supplemental lighting duration for the next hour was determined by the difference between the target HLI and the actual HLI from all previous periods. Furthermore, the supplementary lighting strategy incorporated maximum values for both PPFD and temperature, and the supplemental light was withheld whenever the actual PPFD or temperature exceeded these values. An experiment was conducted on strawberries in a commercial greenhouse, targeting a DLI of 12.6 mol/(m2∙d), with no supplemental lighting as the control. The results indicated that LED supplemental lighting based on HLI increased the DLI to approximately10 mol/(m2∙d) and raised the strawberry canopy temperature by 1°C-2°C. Compared to the control treatment, the LED supplemental lighting based on HLI significantly improved the net photosynthetic rate, stem thickness, number of leaves, leaf length, and leaf width of the strawberry plants. Additionally, the fruit yield per plant, soluble solids content, and sugar-acid ratio in the supplemental lighting treatment increased by 32%, 21%, and 33%, respectively. Thus, LED supplemental lighting based on HLI is an effective strategy for improving the yield and quality of greenhouse crop production. Keywords: daily light integral, hourly light integral, greenhouse strawberry, LED supplementary strategy, temperature coupling control DOI: 10.25165/j.ijabe.20241705.8900 Citation: Yang R M, Qiu C H, Zheng J F, Ji F, He D X, Yang P. LED supplementary strategy based on hourly light integral for improving the yield and quality of greenhouse strawberries. Int J Agric & Biol Eng, 2024; 17(5): 96-104.